Experimental Investigation about the Effects of Blockage on Upstream Box Culverts (Journal of Engineering, 2024)
This experimental study focuses on scouring in box culvert inlets under steady-state conditions and at different percentages of blockage ranging from 0% to 65%, and also looks at the hydraulics of water in the culvert. The investigation shows that the blockage of the culverts has influenced the scouring pattern at the blocked culverts' entrances. Ten experiments were carried out at the laboratory to see how blockage impacts the scouring pattern upstream of a box culvert during steady flow. Both partially blocked and unblocked cases were implemented in this study. The experimental tests were done until the equilibrium scour occurred, which took about 3.5 hours of water flow to reach equilibrium conditions.  The results revealed that the blockage will increase the water depth at the inlet by about 30%–50%, which may affect the safety of structures or cause culvert failure. In addition, the results discovered that the maximum scour depth, which inversely correlated with the obstruction upstream of the box culvert, increased with increasing discharge.